Bathymetric and longitudinal distribution analyysis of the rockfish Helicolenus Dactylopterus (Delaroche, 1809) in the southern Tyrrhenian Sea (central Mediterranean) - ROMEO, T.; CASTRIOTA, L.; CONSOLI, P.; FALAUTANO, M.; FLORIO, G.; PERDICHIZZI, F.; FINOIA, M.G.; ANDALORO, F.; RINELLI, P. (Mediterranean Marine Science, 2009)
This study provides information on bathymetric and longitudinal distribution heterogeneity of the rockfish Helicolenus dactylopterus in the southern Tyrrhenian Sea. Data were drawn from experimental bottom trawl (1996-2002) plus bottom trap (2001-02) surveys. The frequency of occurrence and mean relative density (N/km2) and biomass (kg/km2) indexes were calculated for two survey seasons (spring and autumn), four geographic sectors and three depth strata. MANOVA was used to test fish abundance among years, sectors and strata. Analysis of the length-frequency distributions was carried out by two-way (gears and depths) ANOVA, post hoc multiple comparisons for testing differences among depths and Student’s t test for testing differences between gears. Length-weight relationship was also estimated and the allometric coefficient was tested with the Student’s t test. The results showed a significant positive bathymetric gradient of sizes both for trawl and trap surveys; at same depths, fish caught by traps were significantly longer than those caught by trawl. In spring surveys, significant differences were found among strata for both abundance indexes; in autumn surveys, significant differences between depth strata were found only for density indices. The distribution and abundance patterns of H. dactylopterus along the southern Tyrrhenian Sea was homogeneous among sectors. Length-weight relationship showed a significant positive allometric growth.